2014
DOI: 10.1007/jhep11(2014)054
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and dark force in the type-I inert 2HDM with local U(1) H gauge symmetry

Abstract: We discuss dark matter (DM) physics in the Type-I inert two-Higgs-doublet model (2HDM) with local U(1) H Higgs gauge symmetry, which is assigned to the extra Higgs doublet in order to avoid the Higgs-mediated flavor problems. In this gauged inert DM setup, a U(1) H -charged scalar Φ is also introduced to break U(1) H spontaneously through its nonzero vacuum expectation value (VEV), Φ , and then the remnant discrete subgroup appears according to the U(1) H charge assignment of Φ. The U(1) H -charged Higgs doubl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 115 publications
0
25
0
Order By: Relevance
“…The popular choice is a discrete symmetry, such as Z 2 on the second Higgs doublet in IHDM or 2HDM type-I [22,23], type-II [23,24], type-X and type-Y [25][26][27] where some of SM fermions are also odd under Z 2 unlike IHDM. The other choice is a continuous symmetry, such as a local U(1) symmetry discussed in [28][29][30][31]. The FCNC constraints can be avoided by satisfying the alignment condition of the Yukawa couplings [32] to eliminating dangerous tree-level contributions although it is not radiatively stable [33].…”
Section: Jhep04(2016)019mentioning
confidence: 99%
“…The popular choice is a discrete symmetry, such as Z 2 on the second Higgs doublet in IHDM or 2HDM type-I [22,23], type-II [23,24], type-X and type-Y [25][26][27] where some of SM fermions are also odd under Z 2 unlike IHDM. The other choice is a continuous symmetry, such as a local U(1) symmetry discussed in [28][29][30][31]. The FCNC constraints can be avoided by satisfying the alignment condition of the Yukawa couplings [32] to eliminating dangerous tree-level contributions although it is not radiatively stable [33].…”
Section: Jhep04(2016)019mentioning
confidence: 99%
“…[14]. Also they constructed the inert 2HDM model with U(1) H gauge symmetry and showed that the light dark matter (DM) mass region below ∼ m W is widely open if the Z 2 symmetry is implemented into local U(1) H gauge symmetry, due to newly open annihilation channels of the DM pair into the extra U(1) H gauge boson(s): HH → Z H Z H , ZZ H , which are not present in the ordinary inert 2HDM with discrete Z 2 symmetry [18]. In fact this phenomenon is very generic in dark matter models with local dark gauge symmetries [19][20][21][22][23][24].…”
Section: Jhep06(2015)034mentioning
confidence: 99%
“…On the other hand, some of them might be stable (or long-lived enough) and could be good cold dark matter (CDM) candidates as pointed out in refs. [15,18]. Their stability could be guaranteed by the remnant symmetry of U(1) H [18].…”
Section: Jhep06(2015)034mentioning
confidence: 99%
“…Nevertheless, some proposals to extend the 2HDM via the presence of gauge symmetries have been put forth [43][44][45]. Some were triggered by anomalies in flavor and collider physics [46][47][48] and others devoted to explain neutrino masses via type I seesaw mechanism and absence of flavor changing interactions [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%